2005
DOI: 10.1007/s10711-004-4197-6
|View full text |Cite
|
Sign up to set email alerts
|

Projective Completions of Jordan Pairs, Part II: Manifold Structures and Symmetric Spaces

Abstract: Abstract. We define symmetric spaces in arbitrary dimension and over arbitrary non-discrete topological fields K , and we construct manifolds and symmetric spaces associated to topological continuous quasi-inverse Jordan pairs and -triple systems. This class of spaces, called smooth generalized projective geometries, generalizes the well-known (finite or infinite-dimensional) bounded symmetric domains as well as their "compact-like" duals. An interpretation of such geometries as models of Quantum Mechanics is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
6
1
1

Relationship

6
2

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 31 publications
(26 reference statements)
0
38
0
Order By: Relevance
“…alternative algebras or Jordan systems) in order to obtain a kind of "chain geometry". We refer to [11], [12], [18], [19], [20], [21], [28], [40,Chapter 3], [41], and [68].…”
Section: 63mentioning
confidence: 99%
“…alternative algebras or Jordan systems) in order to obtain a kind of "chain geometry". We refer to [11], [12], [18], [19], [20], [21], [28], [40,Chapter 3], [41], and [68].…”
Section: 63mentioning
confidence: 99%
“…Then the involution * lifts to an involution of the projective line AP 1 whose fixed point set is called the Hermitian projective line, see [BeNe05]. Let us give here a slightly modified version of the construction given in loc.…”
Section: The Hermitian Projective Linementioning
confidence: 99%
“…Moreover, it is also shown that G A /G A (p) is a complexification of U A /U A (p), and then these results are translated in terms of homogeneous vector bundles, in the spirit of Theorem 5.8 in [5]. (A complementary perspective on these manifolds can be found in [6].) Section 4 is devoted to exhibit how the above results look like in the (on the other hand well known) case of the algebra A = B(H) and corresponding universal, tautological vector bundles.…”
Section: Introductionmentioning
confidence: 99%